FROM PAPER TO DIGITAL: ELECTRONIC SIGNATURE AND RECORD IN THE CONTEXT OF ROMANIAN LEGAL REGULATIONS - Morozan, Florina Florentina (International Journal of Legal and Social Order, 2025)
The transition from traditional written forms to electronic communication has accelerated in recent years, particularly due to the expansion of teleworking and the widespread use of remotely concluded contracts. These developments necessitated a coherent legal framework governing the creation, transmission, and evidentiary value of electronic documents and electronic signatures. Romania aligned early with European trends and progressively modernized its legislation to ensure the authenticity, integrity, and legal certainty of digital documents. A decisive step in this evolution is represented by Law No. 214/2024, which harmonizes national rules with the eIDAS Regulation and introduces essential updates to the Code of Civil Procedure. The new law modernizes and unifies previous regulations, adapting them to the current technological context and facilitating the interoperability of digital solutions at the European level. This study presents the evolution of European and Romanian regulations applicable to electronic documents and electronic signatures, emphasizing the implications for judicial practice and the challenges courts have encountered during this transition. The paper highlights the need for a technologically neutral and predictable legal framework capable of supporting the digitalization of civil procedures and private law relations while safeguarding fundamental procedural rights.